A High-Power Radar Rotary Joint - Zhang, Zhiqiang; Xue, Kaibin; Weng, Zibin (Frontiers in Physics, 2022)
Due to the power capacity limitation of the rotary joint, mechanical scanning radars are limited to use high-power microwave sources to improve their performance furthermore. To solve this problem, an over-mode circular waveguide rotary joint with radial mutations at the rotation point is introduced in this letter. The structure of the radial mutation is optimized to suppress unwanted modes. By connecting the choke slot and the rotating part, the breakdown risk of the rotary joint can be reduced. In addition, the choke structure is connected to the inner wall of the waveguide with a gap, even the breakdown occurs in the choke, the normal modes inside the waveguide will not be affected. To verify the design, a prototype of the rotary joint is fabricated and measured with the operating band in the range of 9.5GHz - 10.5 GHz and a power capacity of 3GW.